2015
DOI: 10.9734/bjmmr/2015/15908
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycaemic Effect of Lycopene in Streptozotocin-Induced Diabetic Wistar Rats

Abstract: Aim:The study was designed to investigate the hypoglycaemic potential of lycopene in streptozotocin (STZ)-induced diabetic Wistar rats. Methodology: To achieve this, a total of thirty (30) adult Wistar rats of both sexes were used. The animals were made diabetic by single intraperitoneal injection of freshly prepared (60 mg/kg body weight) of STZ. Diabetes was confirmed by the presence of high blood glucose ≥ 200 after 72 hr. Diabetic animals were divided into six ( 6) groups (1, 2, 3, 4, 5 and 6) comprising f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Lycopene is the most predominant carotenoid in tomatoes and has the highest antioxidant property among all dietary carotenoids (Rao and Agrawal, 1999). Studies reported on lycopene's effects in STZ-induced diabetic animals included altered thyroid profile (Eze et al, 2015a), atherogenic cardiovascular risk (Eze et al, 2015b), kidney antioxidant enzyme activity (Eze et al, 2015c), a hypoglycemic effect (Eze et al, 2015d), altered liver markers and glucokinase activity of diabetic animals (Eze et al, 2016) as well as histological changes (Soleymaninejad et al, 2017). Haribabu et al (2013) found that lycopene at 2 and 4 mg/kg body weight in combination with glipizide and metformin had antidiabetic activity on the 21st day of treatment in alloxaninduced diabetic rats.…”
Section: Introductionmentioning
confidence: 99%
“…Lycopene is the most predominant carotenoid in tomatoes and has the highest antioxidant property among all dietary carotenoids (Rao and Agrawal, 1999). Studies reported on lycopene's effects in STZ-induced diabetic animals included altered thyroid profile (Eze et al, 2015a), atherogenic cardiovascular risk (Eze et al, 2015b), kidney antioxidant enzyme activity (Eze et al, 2015c), a hypoglycemic effect (Eze et al, 2015d), altered liver markers and glucokinase activity of diabetic animals (Eze et al, 2016) as well as histological changes (Soleymaninejad et al, 2017). Haribabu et al (2013) found that lycopene at 2 and 4 mg/kg body weight in combination with glipizide and metformin had antidiabetic activity on the 21st day of treatment in alloxaninduced diabetic rats.…”
Section: Introductionmentioning
confidence: 99%
“…18,22 The large number of conjugated double bonds in lycopene makes it a potent antioxidant because the delocalization of π electrons that occurs along the double bond allows the neutralization reaction of molecules containing unpaired electrons. 19,35 The radical neutralization reaction of lycopene can occur in various ways, including adding radicals to the polyene chain, electron transfer from lycopene to radicals, or eliminating hydrogen atoms from lycopene. 41 These three reactions are explained in succession as follows: (i) adding radicals to the polyene chain of lycopene: Lycopene + R• R-Lycopene•, (ii) electron transfer from lycopene to the radical: Lycopene + R• Lycopene •+ + Rand (iii) hydrogen elimination from lycopene: Lycopene + R•  Lycopene• + RH.…”
Section: Lycopene Ameliorates Oxidative Stress In Dmmentioning
confidence: 99%
“…16 The large number of conjugated double bonds that lycopene has is the basis of its antioxidant properties. [17][18][19] Moreover, lycopene also has anti-inflammatory effects. Many studies have shown that lycopene shows potential beneficial effects in cancer and lifelong diseases, such as cardiovascular, neurodegenerative, and metabolic diseases which includes diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…DISCUSSION: The present study revealed a dosespecific pharmacologic activity of the aqueous leaf extract of N. laevis at 100 and 200 mg/kg body weight. Alloxan monohydrate is a hydrophilic and unstable compound of glucose analogues that specifically accumulate in pancreatic β-cells via the Glucose Transporter 2 41 to induce hyperglycaemia (type I diabetes) 9,42 . The cytotoxic activity of alloxan monohydrate involves oxidation of essential sulphydryl (-SH) group, inhibition of glucokinase enzymes, generation of free radicals and disturbance of intracellular calcium homeostasis 42 .…”
Section: Day 14mentioning
confidence: 99%
“…Diabetes mellitus is therefore a group of metabolic diseases characterized by hyperglycemia, resulting from defects in insulin secretion, insulin action, or both. Report have it that protection against the alloxan-induced hyperglycaemia can be achieved by a combination of superoxide dismutase and catalase, which completely prevents redox imbalance between alloxan, ROS species generation and antioxidant status 9,10 . Studies have also been reported in the open scientific literature on induced hyperglycaemia following administration of alloxan and or extracts of medicinal plants 5,11,12,13,14 .…”
mentioning
confidence: 99%